Understanding Readmission Risks in End-Stage Kidney Disease: A Study from Wangaya Hospital - Dewi, Ni Nyoman Gita Kharisma; Pratiwi, Made Sindy Astri; Agustini, Made Priska Arya; Dewi, Putu Itta Sandi Lesmana; Fahira, Cindy; Sunaka, I Wayan (Indonesian Journal of Kidney and Hypertension, 2025)
Background: End-stage kidney disease (ESKD) is a growing health burden. Poor patient knowledge and treatment adherence contribute to increased morbidity, as reflected in readmission rates. Objective: This study aimed to identify factors associated with readmission among ESKD patients in Bali. Methods: A retrospective cohort study was conducted at Wangaya Hospital. Adult patients (≥18 years) diagnosed with ESKD, with or without dialysis, between 2022 and 2024 were included. Patients with incomplete records or a solitary kidney were excluded. Bivariate analysis (chi-square test) and multivariate analysis (binary logistic regression) were used to assess associations, with significance set at p <0.05. Results: A total of 199 patients met the inclusion criteria; 61.8% were male, with a median age of 57 years (range: 22–88 years). Readmission rates within and beyond one month were 18.6% and 15.1%, respectively. Reduced eGFR was significantly associated with 30-day readmission (p = 0.041). For readmission beyond 30 days, significant predictors included diabetes mellitus (p = 0.014), neurologic disorders (p < 0.001), and adherence (p = 0.019). Conclusion: eGFR predicts early readmission, while diabetes mellitus, neurological disorders, and treatment adherence influence later readmissions. Identifying these factors is vital for improving patient education and reducing healthcare burdens.